Isolation and Structure Determination of Stigmaterol from the Stem Bark of Lansium domesticum Corr. Cv. Kokossan - Siska Elisahbet Sinaga; Fajar Fauzi Abdullah; Unang Supratman; Tri Mayanti; Rani Maharani (Chimica et Natura Acta, 2022)
Indonesia is a tropical country with biodiversity and a source of natural compounds such as terpenoids, phenolic, flavonoids, and alkaloid groups. The steroid is one of the large groups of terpenoid compounds with various structures and bioactivities. The steroid was also commonly found in the Meliaceae family. One species of this family is Lansium domesticum Corr. which has been studied to have various activities from isolated compounds (limonoids, sesquiterpenoids, onoceranoids, cycloartanoids, and steroids) as well as from their extracts such as antidiarrheal, antimalarial, antimicrobial, antiinsecticide, antifeedant and were used as traditional medicine such as eye drops and scorpion stings. The n-hexane fraction from the bark of L. domesticum Cor. cv. Kokosan produced steroid compounds whose structure is determined by IR, 1H-NMR, 13C-NMR, and DEPT spectroscopy methods and compared with the literature. It was concluded that the steroid isolated was (22E)-stigmasta-5,22-dien-3ol and was first isolated from this genus. This compound was inactive against MCF-7 breast cancer cells with an IC50 value of 832.14 µM.